To Catch a Lawsuit: Constitutional Principles at Work in the Investigative-Journalism Genre - Dearington, Michael F. (2012)
This Note examines two causes of action, civil rights violations under 42 U.S.C. § 1983 and II ED claims, in the context of lawsuits against investigative journalists. Examining two recent cases in particular, Tiwari v. NBC Universal, Inc. and Conradt v. NBC Universal, Inc., which arise out of NBC's conduct in its primetime series To Catch a Predator, this Note concludes that legal standards governing conduct by investigative journalists are currently unclear. Investigative journalists are not adequately on notice as to when they might be liable under § 1983 for violating a subject's civil rights. And district courts have failed to appreciate journalists' First Amendment rights when analyzing II ED claims. Ultimately, this Note advocates for a media influence test that analyzes whether a journalist should be liable for civil rights violations under § 1983 and concludes that courts must exclude journalists' ability to widely disseminate information as a position of power when analyzing outrageousness alleged in II ED claims